The effect of the quality of coronal restoration versus the quality of root canal filling on periapical health: systematic review and meta-analysis - Elif Bahar ÇAKICI; Fatih ÇAKICI (Gazi University, 2022)
Objective: The aim of this meta-analysis was to compare the impact of the quality of root canal treatment versus the quality of coronal restoration on periapical health. Materials and Method: A literature review was conducted using the search terms "endodontics", "periapical index", "periapical status", "quality of root canal treatment", "root treatment", "root canal treatment", "coronal restoration", "quality of root canal treatment", "cone beam computed tomography", and "restoration". The studies evaluating the effect of the quality of root canal filling and the quality of coronal restoration on periapical tissues were selected. Data were collected by two researchers according to the inclusion and exclusion criteria. The ratio of teeth with apical periodontitis was recorded for each category: adequate root canal treatment (AC), inadequate root canal treatment (IC), adequate restoration (AR), and inadequate restoration (IR). The data were analyzed using meta-analysis for odds ratios. The significance level was set at α=0.05. Results: There were statistically significant differences between AC-IR and AC-AR [p=0.02 and OR=1.88, 95% confidence interval (CI): 1.13-3.13], between IC-AR and AC-AR [p=0.006 and OR=3.23 (1.41-7.39)], between IC-IR and AC-AR [p<0.00001 and OR=5.18 (2.62-10.23)], between IC-AR and AC- IR [p=0.02 and OR=1.48 (1.07-2.03)], between IC-IR and AC-IR [p<0.0001 and OR=2.44 (1.69-3.51)], between IC-IR and IC-AR [p<0.00001 and OR=1.80 (1.38-2.34)] Conclusion: On the basis of the current best available evidence, the odds for the healing of apical periodontitis increases with both adequate root canal treatment and adequate restorative treatment. When AC-IR versus IC-AR was evaluated, it was revealed that root canal filling was more important than coronal restoration.